2018
DOI: 10.1016/j.eats.2017.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Superior Peroneal Retinaculum Reconstruction

Abstract: Post-traumatic peroneal tendon subluxation or dislocation is most commonly due to injury to the superior peroneal retinaculum. Acute repair of the retinaculum is an option for active athletes who desire quick return of sport activity. In general, conventional open surgeries require extensive exposure of the injured superficial peroneal retinaculum and have potential risks of scar formation, sural nerve injury, limited range of movement, peroneal tendon re-subluxation, and tendon irritation. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 33 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…The results of our study may have important clinical implications. These connections may explain various combinations commonly encountered in lateral ankle instability patterns ( 3 , 6 8 , 29 ) . It has been suggested that a disruption of the lateral collateral ligaments induces strain and injury on the SPR, which may explain why the conditions commonly coexist ( 8 ) .…”
Section: Discussionmentioning
confidence: 94%
“…The results of our study may have important clinical implications. These connections may explain various combinations commonly encountered in lateral ankle instability patterns ( 3 , 6 8 , 29 ) . It has been suggested that a disruption of the lateral collateral ligaments induces strain and injury on the SPR, which may explain why the conditions commonly coexist ( 8 ) .…”
Section: Discussionmentioning
confidence: 94%
“…Second, the current procedure does not require an incision to the SPR to improve healing through better preservation of the blood supply, and less peritendinous fibrosis will not cause tendon irritation and adherence after the operation. The endoscopic procedure also requires no incision to the SPR and is less invasive, though technically demanding and involves a steep learning curve [ 11 , 18 ]. Current procedure has advantage in ts ease of learning compared to endoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The described endoscopic approach has the advantages of better cosmetic results, less pain, less surgical trauma, and the possibility of dealing with associated pathologies (e.g., peroneal tendon tear or instability) endoscopically. 6,9,[13][14][15][16] The potential risks of this technique include injury to the peroneal tendons, superior peroneal retinaculum, and sural nerve ( Table 3). This technique is not technically demanding and can be attempted by the average foot and ankle arthroscopist.…”
Section: Discussionmentioning
confidence: 99%
“…If instability of the peroneal tendons is noted, endoscopic reconstruction of the superior peroneal retinaculum can be performed via the same portals. 13,14 Postoperatively, free mobilization is allowed if retinaculum reconstruction is not performed. If retinaculum reconstruction is performed, the ankle is immobilized in a short leg cast for 3 weeks.…”
Section: Resection Of Peroneus Quartusmentioning
confidence: 99%